The high oil price and the recycling of OPEC petrodollars: Looming dangers for the international financial markets? - Enno Harks (Stiftung Wissenschaft und Politik (SWP), 2005)
High oil prices have made OPEC earn record revenues during the last couple of years. Due to the low absorptive capacity of oil-exporting economies, a good portion of this income is invested in international financial markets. During the last period of high oil prices, the oil shocks of the Seventies, recycling of petrodollars brought turmoil to financial markets and triggered the first international debt crisis at the beginning of the 1980's. An analysis of today's situation indicates that current oil revenues do not yet have harmful impacts on the stability of international financial markets. However, due to the situation of world crude oil market in 2005, dangers may be looming in the not so distant future. (SWP-Comments / SWP)
Keywords: 320